Doula Assistance In Preventing Postpartum Blues: Mix Methods Study - Legina Anggraeni; Made Gita Hermawati; Royani Chairiyah (JURNAL KEBIDANAN, 2022)
After childbirth, a woman goes through a transition period for her new role as a mother. Hormonal and psychological factors cause many changes in the mother's body. These changes will cause a disappointed, worried, and anxious mood. This atmosphere is referred to as postpartum blues, and if not handled correctly, this is very dangerous for the condition of the mother and baby. The study aimed to look at the benefits of mentoring provided by doulas to reduce postpartum blues in postpartum mothers. The methods used are quantitative and qualitative while, the research locations are in the city of Jakarta, Depok, and Tanggerang. Quantitative studies were conducted on 50 samples, and the data was then processed using univariate and bivariate. While informant qualitative research as many as 13 informants consisting of doulas, postoartum mothers accompanied by doulas along with their husbands with a total of 13 informants. This study showed that the variables of age, parity, knowledge, and doula assistance were significantly related. Doula assistance is beneficial for postpartum mothers and their families, significantly reducing or eliminating postpartum blues symptoms. The advice of this study is that the concept of doula assistance is necessary and can be done by the husband or closest family of the postpartum mother.